2011
DOI: 10.1371/journal.pone.0021557
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Assembly Checkpoint Regulates Mitotic Cell Cycle Progression during Preimplantation Embryo Development

Abstract: Errors in chromosome segregation or distribution may result in aneuploid embryo formation, which causes implantation failure, spontaneous abortion, genetic diseases, or embryo death. Embryonic aneuploidy occurs when chromosome aberrations are present in gametes or early embryos. To date, it is still unclear whether the spindle assembly checkpoint (SAC) is required for the regulation of mitotic cell cycle progression to ensure mitotic fidelity during preimplantation development. In this study, using overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 40 publications
(64 reference statements)
0
53
0
Order By: Relevance
“…Several checkpoints control the proper alignment of chromosomes during mitosis and meiosis and block entry into anaphase when the chromosomes are not appropriately attached to the spindle (Encalada et al 2005, Wei et al 2011. However, these mechanisms may be deficient to avoid all the errors, supported by findings of lagging chromosomes in human embryos (Coonen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several checkpoints control the proper alignment of chromosomes during mitosis and meiosis and block entry into anaphase when the chromosomes are not appropriately attached to the spindle (Encalada et al 2005, Wei et al 2011. However, these mechanisms may be deficient to avoid all the errors, supported by findings of lagging chromosomes in human embryos (Coonen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficiency of the in-house locus-specific probes was pre-validated using mitotic metaphase chromosomes of cultured peripheral blood lymphocytes, they may be suboptimal with interphase nuclei of single blastomeres. Alternatively, chromosomal repair processes such as mitotic checkpoints (Encalada et al 2005, Wei et al 2011) and reabsorption of chromosomecontaining cytoplasmic debris (Chavez et al 2012), which are active during embryonic development to the blastocyst stage, may be involved. The percentage of chromosomally balanced blastocysts observed in the present study (w60%) exceeds the predicted incidence of Rob carriers (1/6 normal, 1/6 carrier) (Bint et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lagging chromosomes in anaphase may be due to the depletion and/or reduced stringency of the spindle assembly complex in oocytes and early preimplantation embryos, which rely on maternally supplied spindle assembly complex mRNAs and proteins until EGA. Evidence for this is provided by mouse embryo studies showing that the knockdown of the spindle assembly complex components, Bub3, BubR1, and Mad2, leads to improper chromosome segregation, aneuploidy generation, and the formation of micronuclei, or small nuclei that encapsulate chromosomes or pieces of chromosomes that failed to incorporate into the primary nucleus of one of the daughter cells during division (Wei et al 2011). Furthermore, additional studies have demonstrated that chromosome lagging commonly arises from the formation of merotelic attachments in mitosis, whereby a single kinetochore on one side of the chromosome is attached to microtubules emanating from both spindle poles (for a review, see Gregan et al 2011).…”
Section: Potential Mechanisms Of Aneuploidy Generationmentioning
confidence: 99%
“…There is an enormous variation in the rate of mitotic slippage in different cell types. This large variation is well illustrated by the difference in SAC responses in newly fertilized embryonic cells of different metazoans: some embryos, such as those of Xenopus laevis or Danio rerio , display no SAC response during early embryonic divisions (Hara et al, 1980; Zhang et al, 2015); other embryonic cells, such as those of newly fertilized C. elegans or Lytechinus variegatus (green sea urchin) embryos, exhibit only moderate mitotic delays (Encalada et al, 2005; Sluder, 1979); and others, such as those of Mus musculus , Arbacia punctulata (purple-spined sea urchin) and Spisula solidissima (atlantic surf clam), seem to display strong checkpoint responses from the start of embryogenesis (Evans et al, 1983; Hunt et al, 1992; Siracusa et al, 1980; Wei et al, 2011). The absence of SAC signaling in some early embryonic divisions has been attributed to a developmental timer that only switches on SAC signaling at later stages of development, around the onset of gastrulation (Clute and Masui, 1995, 1997; Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%